Localized delivery of CRISPR/dCas9 via layer-by-layer self-assembling peptide coating on nanofibers for neural tissue engineering - Zhang, Kunyu (2020)
The clustered regularly interspaced short palindromic repeat (CRISPR) systems have a wide variety of applications besides precise genome editing. In particular, the CRISPR/dCas9 system can be used to control specific gene expression by CRISPR activation (CRISPRa) or interference (CRISPRi). However, the safety concerns associated with viral vectors and the possible off-target issues of systemic administration remain huge concerns to be safe delivery methods for CRISPR/Cas9 systems. In this study, a layer-by-layer (LbL) self-assembling peptide (SAP) coating on nanofibers is developed to mediate localized delivery of CRISPR/dCas9 systems. Specifically, an amphiphilic negatively charged SAP− is first coated onto PCL nanofibers through strong hydrophobic interactions, and the pDNA complexes and positively charged SAP+-RGD are then absorbed via electrostatic interactions. The SAP-coated scaffolds facilitate efficient loading and sustained release of the pDNA complexes, while enhancing cell adhesion and proliferation. As a proof of concept, the scaffolds are used to activate GDNF expression in mammalian cells, and the secreted GDNF subsequently promotes neurite outgrowth of rat neurons. These promising results suggest that the LbL self-assembling peptide coated nanofibers can be a new route to establish a bioactive interface, which provides a simple and efficient platform for the delivery of CRISPR/dCas9 systems for regenerative medicine.